Synthesis, Molecular Docking, and Evaluation of Some New Curcumin Analogs as Antimalarial Agents - Endang Astuti; Tri Joko Raharjo; Putra Boang Manalu; Ilham Satria Putra; Stephanus Satria Waskitha; Junita Solin (Indonesian Journal of Chemistry, 2021)
This research involves the synthesis, antimalarial evaluation, and molecular docking of several curcumin analogs. A total of six curcumin analog compounds were synthesized using aldol condensation using hydrochloric acid and sodium hydroxide catalysts. The synthesized compounds were elucidated using FTIR, 1H-NMR, 13C-NMR, and LC-MS/MS. Subsequently, all curcumin analogs were tested as an antimalarial agent against Plasmodium falciparum 3D7 strain, and their mechanism of action was evaluated through a molecular docking study. Six curcumin analogs, i.e. 2,6-bis(2-hydroxybenzylidene)cyclohexanone; 2,6-bis(2-hydroxybenzylidene)cyclopentanone; 1.5-bis(2-hydroxyphenyl)penta-1,4-diene-3-one; 2,6-bis(3-hydroxybenzylidene)cyclo-hexanone; 2,6-bis(3-hydroxybenzylidene)cyclopentanone; and 1,5-bis(3-hydroxy-phenyl)penta-1,4-diene-3-one have been successfully synthesized. In addition, 2,6-bis(2-hydroxybenzylidene) cyclopentanone demonstrated the lowest IC50 value and binding affinity of 0.04 µM and -7.6 kcal/mol, respectively. Based on molecular docking studies, this compound also showed the most potent antimalarial activity targeted at PfATP6.